Shakhṣiyyat al-Baṭal ar-Raʾīsī fī Riwāyat “al-Jāḥid” lil Ḥasan al-Bukhārī: Dirāsah Nafsiyyah Insāniyyah lil Abrāhām Māzlū: The Personality of the Main Character in the Novel "Al-Jahid" by Hasan Al-Bukhari: A Humanistic Psychological Study of Abraham Maslow." - Anggraini, Reza; Rohanda, Rohanda; Mawardi (An-Nahdah Al-'Arabiyah, 2025)
This research aims to analyze the personality of the main character Hadi in the novel Al-Jahid by Al-Hasan Al-Bukhari using Abraham Maslow's theory. The novel Al-Jahid was chosen as the object of study because it depicts the journey of human life which is full of challenges, conflicts and struggles to meet life's needs. This is in accordance with Abraham Maslow's theory which discusses the hierarchy of human needs, starting from physiological needs to self-actualization. This research uses a descriptive method of content analysis, with data collection through library study techniques. The results of the analysis show that Hadi fulfills various levels of needs in Maslow's hierarchy, starting from basic needs such as security, to social needs in the form of affection and acceptance. At a higher level, Hadi's character stands out in the aspects of self-esteem and self-actualization, which are reflected in his intelligence, wisdom and responsibility towards life. This research provides insight into how Maslow's hierarchy of needs structure can be applied to understanding characters in literary works.  يهدف هذا البحث إلى تحليل شخصية البطل هادي في رواية "الجاحد" للحسن البخاري باستخدام نظرية أبراهام ماسلو. تم اختيار رواية "الجاحد" كموضوع للدراسة لأنها تصور رحلة الحياة البشرية المليئة بالتحديات والصراعات والكفاح من أجل تلبية احتياجات الحياة. وهذا يتوافق مع نظرية أبراهام ماسلو التي تناقش تسلسل الاحتياجات البشرية، بدءًا من الاحتياجات الفسيولوجية وصولًا إلى تحقيق الذات. يستخدم هذا البحث منهجًا وصفيًا لتحليل المحتوى، مع جمع البيانات من خلال دراسة المصادر المكتبية. وتظهر نتائج التحليل أن هادي يحقق مختلف مستويات الاحتياجات في تسلسل ماسلو، بدءًا من الاحتياجات الأساسية مثل الأمان، ثم الاحتياجات الاجتماعية مثل المودة والقبول. وعلى مستوى أعلى، تبرز شخصية هادي في جوانب تقدير الذات وتحقيق الذات، والتي تنعكس في ذكائه وحكمته ومسؤوليته تجاه الحياة. يوفر هذا البحث رؤية حول كيفية تطبيق تسلسل احتياجات ماسلو لفهم الشخصيات في الأعمال الأدبية. Penelitian ini bertujuan untuk menganalisis kepribadian tokoh utama Hadi dalam novel Al-Jahid karya Al-Hasan Al-Bukhari dengan menggunakan teori Abraham Maslow. Novel Al-Jahid dipilih sebagai objek kajian karena menggambarkan perjalanan hidup manusia yang penuh dengan tantangan, konflik, dan perjuangan dalam memenuhi kebutuhan hidup. Hal ini sesuai dengan teori Abraham Maslow yang membahas hierarki kebutuhan manusia, mulai dari kebutuhan fisiologis hingga aktualisasi diri. Penelitian ini menggunakan metode deskriptif dengan analisis isi, serta pengumpulan data melalui studi pustaka. Hasil analisis menunjukkan bahwa Hadi memenuhi berbagai tingkat kebutuhan dalam hierarki Maslow, mulai dari kebutuhan dasar seperti keamanan, hingga kebutuhan sosial dalam bentuk kasih sayang dan penerimaan. Pada tingkat yang lebih tinggi, karakter Hadi menonjol dalam aspek penghargaan diri dan aktualisasi diri, yang tercermin dalam kecerdasan, kebijaksanaan, dan tanggung jawabnya terhadap kehidupan. Penelitian ini memberikan wawasan tentang bagaimana struktur hierarki kebutuhan Maslow dapat diterapkan dalam memahami karakter dalam karya sastra.